Parametric Design and Hybrid Fabrication of Above-Knee Prosthesis - Amrutsagar, Lalitrao (Indian J Orthop, 2020)
BACKGROUND: India has a large number of above-knee amputation patients who require a prosthetic leg that is affordable, conformal, functional, and durable. Available low-cost solutions, such as Jaipur foot, employ gypsum plaster in the process of fabricating a fitting socket. This has four shortcomings: (1) requirement of trained technicians, (2) high possibility of manual errors leading to rework, (3) long production time of several hours, and (4) difficulty in scaling up for widespread application. MATERIALS AND METHODS: An improved approach is presented here, which combines computer-aided parametric design and numerically controlled machining with manual thermoforming to overcome the above issues. The socket is semi-automatically designed based on 60 parameters, derived from 23 measurements obtained on the natural stump of a patient. The three-dimensional (3D) computer-aided design model of the socket can be used for additive manufacturing (3D printing), which was found to be accurate, but time-consuming and expensive. Hence, a hybrid process was evolved with the following three steps: computer numeric control machining of the stump and shank replica in polyurethane (PU) foam, followed by coating with suitable epoxy, and finally high-density polyethylene pipe thermoforming over the PU foam replicas. RESULTS: Three prostheses were fabricated using both conventional and hybrid processes and provided to volunteer patients. The hybrid process resulted in 28% reduction in overall fabrication time and improved satisfaction of patients due to better fit and comfort. CONCLUSION: The proposed approach can be adapted for mass customization, required to meet the large gap in demand and supply, especially in resource-constrained settings.